New Insights into Tumor-Infiltrating B Lymphocytes in Breast Cancer: Clinical Impacts and Regulatory Mechanisms - Shen, Meng; Wang, Jian; Ren, Xiubao (Frontiers in Immunology, 2018)
Currently, tumor-infiltrating B lymphocytes have been recognized as a new hallmark of breast cancer. The function seems to be controversial, either with positive, negative or no significance in breast cancer’s prediction and prognosis. Moreover, B-cell infiltrates regulate tumor process through productions of antibodies and interleukin-10. The interactions with other lymphocytes and PD-1/PD-1 ligand axis are also documented. The regulatory mechanisms will eventually be incorporated into diagnostic and therapeutic algorithms, thus give guide to clinical treatment. In this review, we give new insights into clinical impacts and regulatory mechanisms of tumor-infiltrating B cells, which heralds a new era in immuno-oncology in breast cancer treatment.